2017
DOI: 10.18203/2320-6012.ijrms20170534
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and response of health care workers after needle - stick injury in a tertiary care hospital setting in tribal Rajnandgaon, Chhattisgarh, India

Abstract: Background: Health care workers (HCW) who have occupational exposure to blood are at increased risk for acquiring blood-borne infections. Occupational exposure to blood can result from per-cutaneous injury (needle stick or other sharps injury), muco-cutaneous injury or contact with non-intact skin. Hence not only doctors and nurses even laboratory technicians, housekeeping personnel and hospital waste handlers are at risk of harboring the blood borne infections through needle-stick injury (NSI).Methods: The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
5
6
0
Order By: Relevance
“…In this study, the lifetime NSI pooled prevalence (43.6%) was comparable with studies found from India (40% and 45%) [64, 65], Iran (42.5%) [66], Nigeria (46.0%) [67], Saudi Arabia (46%) [68], and Pakistan (45%) [69]. However, very high prevalence estimates were found from Pakistan (77%) [70], Iran (76%) [71], and India (68.3%) [72].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the lifetime NSI pooled prevalence (43.6%) was comparable with studies found from India (40% and 45%) [64, 65], Iran (42.5%) [66], Nigeria (46.0%) [67], Saudi Arabia (46%) [68], and Pakistan (45%) [69]. However, very high prevalence estimates were found from Pakistan (77%) [70], Iran (76%) [71], and India (68.3%) [72].…”
Section: Discussionsupporting
confidence: 88%
“…Another comprehensive analysis in Iran found an NSI prevalence estimate between 10% and 84.3% (Fereidouni et al, 2018). A study by Yazie et al in Ethiopia reported a pooled NSI prevalence of 43.6% over a person's lifetime, which was similar to those in studies from India (40% and 45.0%) (Farrukh Nagi et al, 2017; Makade et al, 2017; Yazie et al, 2019), Iran (42.5%), Nigeria (46.0%), Saudi Arabia (46%) (Jahan, 2005) and Pakistan (45%) (Afridi et al, 2013). However, extremely high prevalence estimates were observed in Pakistan (77%), Iran (76%) and India (68%) (Archana Lakshmi et al, 2018; Jahangiri et al, 2016; Rais & Jamil, 2013), possibly due to a lack of occupational health and infection prevention training or a lack of suitable or proper personal protective equipment.…”
Section: Discussionsupporting
confidence: 57%
“…(Ashat et al, 2011) Almost twenty diseases can be transmitted by NSI including HBV, HCV and HIV; vaccination is available only for HBV. (Makade, Bhawnani, Verma, & Dengani, 2017) In the 1970s, the risk of acquiring HBV was 10 times greater in HCWs than in the general population; this significantly decline is due, in part, to deliberate vaccination campaign targeting HCWs. (Kuhar et al, 2013) In our study, (10%) of the injured personnel were not immunized at all and (18.6%) were partially immunized against hepatitis B at the time of injury, that put them at potential risk of acquiring HBV (Singhal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of respondents' knowledge of the risks and hazards of NSI, the majority of the respondents (80.4%) scored above average score; which is similar to what had been found in tertiary hospital in India. (Makade et al, 2017) Although the majority (80%) knew that, Hepatitis B vaccine protects against HBV infection; only 47.1% knew that HBV is more contagious than HCV and HIV, and 35.7% knew that HIV is not spread by either shaking hands or sharing same food utensils; which indicate critical level of knowledge about these serious infectious diseases. Physicians were found to have a significantly higher level of knowledge about the risks and hazards of NSI than nurses and technicians, which corresponds to what has been reported in the UK, (Stein, Makarawo, & Ahmad, 2003) This could be explained by the physicians' relatively rich theoretical background, characterizing didactic teaching of the physicians than other medical staff.…”
Section: Discussionmentioning
confidence: 99%